LEVELS OF EDUCATIONAL INFRASTRUCTURE DEVELOPMENT IN AHIRWAL REGION OF HARYANA (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The foundation of development in a country or region is laid by infrastructure. Availability of appropriate infrastructure facilities is an important pre-condition for social and economic development (Patra and Acharya, 2011). The welfare and faster economic growth in rural societies are based on the infrastructure facilities (Sarkar, 2015). Availability of infrastructure has large scale impact on economy of the country and it has huge potential for improving the quality of life. Hence, these services are also referred to as ‘Social Overhead Capital’ (Hirschman, 1958; Rutherford, 2002). The term infrastructure refers to the technical structures that support a society. The development of a region depends upon the development of agriculture and industry but such a development cannot take place without instantaneous development of infrastructure (Naseer, 2004). Infrastructure has various effects on the production activities and quality of life of the people which pervade the entire society (Yoshino and Nakahigashi, 2000). But it requires a long period of time to create these facilities which play instrumental role in social and economic transformation (Ghosh and De, 1998; 2004). Infrastructure provides basic facilities in a specific region and forms the backbone of a country. The term ‘infrastructure’ comprises many activities and it plays a vital role in the industrial and overall economic development (World Bank, 2004). Infrastructure is one of the key inputs in the economic development and in the regions deprived of it the endowment of natural resources become fruitless in ensuring rapid economic development (Kaur and Ghuman, 2009).